The hidden power of provincial and territorial immigration programs in shaping Canada’s immigration landscape - Catherine Xhardez; Danoé Tanguay (Comparative Migration Studies)
Abstract The Canadian immigration system is unique in that subnational governments play a significant role in selecting immigrants through Provincial Nominee Programs (PNPs), which empower nine provinces and two territories to actively select (“nominate”) economic immigrants. Collectively, PNPs have become the country’s largest economic immigration program, but they are also the least studied, leading to a lack of understanding, transparency, and accountability. Using a subnational comparative method, this study examines 78 active subnational immigration programs (policy outputs), investigating policy design, requirements, and distribution of nominations in 2021–2022. We assess whether PNPs contribute to broader changes in the Canadian immigration regime. First, our analysis reveals the prevalence of employment-based streams and prearranged work as a selection criterion. Second, we show nuanced policy outputs in the progression toward a two-step system, with provincial variation in requirements for prior Canadian experience. Third, while PNPs are open to low-skilled workers, programs tailored exclusively to this group remain relatively limited. This comparative analysis reveals significant inter-provincial variation, and highlights the importance of a “disaggregated” evaluation of the migration state at the subnational level.